Posterior reversible encephalopathy syndrome: a study of risk factors, presenting complaints, and magnetic resonance imaging findings from a tertiary care hospital in Pakistan - William, Munna; Anjum, Sadia; Habib, Mudasira; Paudel, Nirmal; Anjum, Abdul Sattar (International Journal of Research in Medical Sciences, 2024)
Background: Posterior reversible encephalopathy syndrome (PRES) primarily occurs in the background of high blood pressure and manifests as symmetrical vasogenic edema involving the parieto-occipital lobes. This study aims to determine the risk factors, presenting complaints, and various typical and atypical radiological patterns of PRES in a larger single-center population. Methods: This is a retrospective observational study of 81 patients with clinical and radiological diagnoses of PRES. Demographic data, concurrent medical illnesses, and presenting complaints were extracted from medical records. Areas of the brain involved and atypical imaging findings were studied on various MR imaging sequences. Results: The most common risk factor was eclampsia (64.20%), followed by renal diseases (16.05%). All but eight cases occurred in the background of hypertension. The most frequent presenting complaint was seizure (79.01%). The most common radiological manifestation was bilaterally symmetrical vasogenic edema, with the parietal lobe (92.59%) and the occipital lobe (83.95%) primarily affected. Restricted diffusion was present in 23.46%, hemorrhage in 8.64%, and post-Gadolinium contrast enhancement in 2.47% of patients. Conclusions: PRES has a diverse clinical and radiological presentation awareness about which among medical professionals is important for timely diagnosis and treatment.